Do Statins Improve Lung Function in Asthmatic Patients? ARandomized and Double-Blind Trial: Role of statins in asthma - Fanak Fahimi; Jamshid Salamzadeh; Solmaz Sohrabi; Hamidreza Jamaati; Atefeh Fakharian; Zohreh Mohammadtaheri (Iranian Journal of Pharmaceutical Sciences, 2009)
There are evidences that statins have anti-inflammatory effects beyond their cholesterol lowering properties. The study was conducted to assess the effects of atorvastatin on asthma as an inflammatory disease. Patients with moderate to sever easthma were entered this randomized, double blind, crossover clinical trial. The impact of oral atorvastatin (10 mg/day) on the lung function of normolipidemic patients was studied. The study was conducted in the National Research Institute of Tuberculosis and Lung Disease. Patients were randomized to receive either atorvastatin or placebo for 4 weeks separated by a 2-week washout period in a crossover fashion.Patients continued on their usual asthma drug treatment throughout the study.Spirometric parameters were determined at baseline and at completion of drug or placebo administration. Seventeen patients with the age of 37.12±12.41 years completed the trial. Data analysis revealed no significant differences in peak expiratory flow rate (PEF), forced expiratory volume in the first second (FEV1),forced vital capacity (FVC) and FEV1/FVC between placebo and atorvastatin therapy. The results showed no significant improvement in the pulmonary function tests in asthmatic patients receiving atorvastatin. Further studies using higher doses of statins and/or higher period of statin use are recommended.